Pengaruh Audit Delay, Spesialisasi Auditor, Reputasi Auditor Terhadap Kualitas Audit Laporan Keuangan Perusahaan Infrastruktur - Della Fitri Yanti; Reni Dwi Widyastuti; Wilda Sari (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
Audit quality is crucial because it determines how effectively auditors can find and report violations in financial statements in accordance with existing standards. However, many cases show irregularities in financial statements due to low audit quality, to test and analyze the impact of audit delays, auditor specialization, and auditor reputation on audit quality in infrastructure companies listed on the Indonesia Stock Exchange for the period 2020-2024. This main problem stems from the many delays in the submission of financial statements and manipulation cases involving infrastructure companies that indicate problems with audit quality. The research method used is quantitative with purposive sampling technique. Data were analyzed using multiple linear regression to see the influence of independent variables on audit quality. The results of this study show that audit delay has an effect on audit quality with a significant value of 0.041 < 0.05, while auditor specialization has an effect on audit quality with a significant value of 0.001 < 0.05 and auditor reputation has no effect on audit quality with a significant value of 0.752 > 0.05. This research is expected to make a theoretical contribution to the development of agency theory and provide practical benefits for investors in assessing the credibility of financial statements in the infrastructure sector.